Optimized in vitro procedure for assessing the cytocompatibility of magnesium-based biomaterials. (1st September 2015) - Jung, Ole; Smeets, Ralf; Porchetta, Dario; Kopp, Alexander; Ptock, Christoph; Müller, Ute; Heiland, Max; Schwade, Max; Behr, Björn; Kröger, Nadja; Kluwe, Lan; Hanken, Henning; et al.
Graphical abstract: Abstract: Magnesium (Mg) is a promising biomaterial for degradable implant applications that has been extensively studied in vitro and in vivo in recent years. In this study, we developed a procedure that allows an optimized and uniform in vitro assessment of the cytocompatibility of Mg-based materials while respecting the standard protocol DIN EN ISO 10993-5:2009. The mouse fibroblast line L-929 was chosen as the preferred assay cell line and MEM supplemented with 10% FCS, penicillin/streptomycin and 4 mMl -glutamine as the favored assay medium. The procedure consists of (1) an indirect assessment of effects of soluble Mg corrosion products in material extracts and (2) a direct assessment of the surface compatibility in terms of cell attachment and cytotoxicity originating from active corrosion processes. The indirect assessment allows the quantification of cell-proliferation (BrdU-assay), viability (XTT-assay) as well as cytotoxicity (LDH-assay) of the mouse fibroblasts incubated with material extracts. Direct assessment visualizes cells attached to the test materials by means of live-dead staining. The colorimetric assays and the visual evaluation complement each other and the combination of both provides an optimized and simple procedure for assessing the cytocompatibility of Mg-based biomaterials in vitro .